Improving Road Safety with Bitumen Emulsion: A Closer Look at Anti-Slip Surfaces - Nurbek Sharibaev; Nosir Sharibaev; Sherzod Djuraev; Sobir Sharipbaev (Genius Journals, 2023)
Bitumen emulsion plays a vital role in improving road safety through the creation of antislip surfaces. This article takes a closer look at the use of bitumen emulsion for enhancing traction and reducing skid resistance on roadways. It highlights the importance of antislip surfaces in preventing accidents and improving vehicle control, especially in areas prone to wet or icy conditions. The article discusses the key factors influencing the effectiveness of anti-slip surfaces, including the selection of aggregates, the emulsion application process, and the maintenance of surface texture. It explores various techniques such as high friction surfacing and microsurfacing that utilize bitumen emulsion to create anti-skid properties. Furthermore, the article examines the benefits and considerations of using bitumen emulsion for anti-slip surfaces, including durability, cost-effectiveness, and environmental impact. By leveraging the potential of bitumen emulsion in creating anti-slip surfaces, road authorities can significantly enhance road safety and minimize accidents.
Keywords: bitumen emulsion; anti-slip surfaces; road safety